The Advantages of Muvon Ecosystem For The Quality of Practicum of SMK Students in Distance Learning: Case Study of Muhammadiyah SMK in Jakarta - Hartono, Bambang Dwi; Akbar, Firman Muhammad Abdurrohman (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to explore the advantages of the Muvon Ecosystem mobile learning application in improving the quality of practicum of SMK students in the context of distance learning. A descriptive qualitative approach is used in this research, with data processing from interviews with respondents consisting of the Head of SMK, Curriculum Staff, Productive Teachers, and Students of SMK Muhammadiyah in DKI Jakarta. The research method is adjusted to the analysis that is measurable and set in a certain period. This research aims to collect primary and secondary data to find facts in the field regarding the need for innovation in the use of mobile learning for vocational practicum through the use of questionnaires as a data collection instrument. The results of this study concluded that respondents showed a positive response to the utilization of the Muvon Ecosystem mobile learning application in distance learning for vocational practicum of vocational students, with a percentage level of agreement of 78%. This shows that Muvon Ecosystem has advantages compared to other mobile learning applications and can be an alternative in carrying out practicum activities with online instructions. Muvon Ecosystem application has a variety of feature facilities such as EduMu, LearningMu, VideoMU, PustakaMU, MessenggerMU, and so on which are very helpful for teachers in implementing practicum learning methods. Another advantage is that Muvon Ecosystem is free to use without requiring payment to become a member for a certain period of time, unlike the RuangGuru application. In addition, the Muvon Ecosystem also allows integration with parents, so parents can control their child's learning activities at school. However, there are drawbacks to Muvon Ecosystem that need to be considered. The main issue that arises is that the network is an obstacle, as not all students are in locations with strong signals. Some students face the problem of weak signals, so learning through the Muvon Ecosystem app stops when the signal becomes weak.